(untitled) (Economic and Political Thought, 2015)
As early as in the period before the enlargement of the European Union in 2004, Poland – as a candidate state at the time – took part in the debate before the European Neighbourhood Policy (formally introduced just a few days after the 2004 enlargement) was conceived. During the debate, the key issue was the idea of further enlargement of the EU after adequate requirements are met. One of the most important elements of the Polish programme within the EU Eastern policy in the period 2006–2014 was energy and activities within the Eastern Partnership. After Sweden supported the Eastern Partnership at its initial stage, Poland gained a lot of positive experience. A supposed permanent element of the Polish strategy within the EU Eastern policy was also its consent for the strengthening of common EU institutions, especially in the internal policy, which might have been interpreted as promoting the principle of “more enlargement for deepening” the co-operation within the EU. It can be perceived as an element of transaction with the member states that were against or sceptical about enlargement and/or an attempt to strengthen Polish stand within the EU Eastern policy with the use of common institutions. A specific canon of the Polish stand within the EU Eastern policy related to the Polish political thought tradition has developed over the last 15 years. From the point of view of the catalogue of Polish targets, one can notice a tendency in the EU to accept some Polish arguments as common ones – it is seen when the development of the idea and implementation of the ENP is compared with what resulted from the Eastern Partnership.